Composite braking module for an electric vehicle - K.R, Bharath; M.K, Sreenivasan; Sivaraman, Gokul; Vineeth Kumar Reddy, Bededala (International Journal of Engineering and Technology, 2018)
The efficycle, is a hybrid tricycle which runs on manual and electric power. This paper proposes a method to design a braking load to dissipate the excess energy produced when there is no more requirement for the battery to be charged by regenerative braking. This module was designed for an operating voltage of 8V, resistance value of 0.16 ohm and with a maximum current capacity of 200 A. This resistor was coupled with a buck converter to step down the voltage across the battery to a value convenient for operation of the dissipation resistor.Â Â